Psychiatric In-Patients Are More Likely to Meet Recommended Levels of Health-Enhancing Physical Activity If They Engage in Exercise and Sport Therapy Programs - Ehrbar, Janine; Brand, Serge; Colledge, Flora; Donath, Lars; Egger, Stephan T.; Hatzinger, Martin; Holsboer-Trachsler, Edith; Imboden, Christian; Schweinfurth, Nina; Vetter, Stefan; Gerber, Markus (Frontiers in Psychiatry, 2018)
Background: People with mental disorders more often engage in sedentary behaviours than healthy controls. In Switzerland, nearly all psychiatric hospitals offer structured exercise and sport therapy as part of their standard therapeutic treatment. However, little is known about the degree to which psychiatric patients make use of these treatment offers. Therefore, this study examines in psychiatric in-patients (a) how many of them participate in structured exercise and sport therapy programs offered by the clinic, (b) engage in exercise and sport activities on an individual basis, and (c) meet recommended levels of health-enhancing physical activity during their stay at the clinic. Furthermore, we examine whether those who engage in exercise and sport activities are more likely to meet internationally accepted physical activity recommendations. Methods: 107 psychiatric in-patients (49% women, Mage=39.9 years) were recruited at three psychiatric clinics in the German-speaking part of Switzerland. All participants were engaged in treatment and received usual care. Based on accelerometer data, participants were classified in two groups who meet vs. do not meet physical activity recommendations ( 150 min of moderate-to-vigorous physical activity per week). Participation in structured and individually performed exercise and sport activities was assessed with the Simple Physical Activity Questionnaire. Results: In total, 57% of all patients met physical activity recommendations. 55% participated in structured exercise and sport therapy activities, whereas only 22% of all patients individually engaged in exercise and sport activities. Psychiatric patients were significantly more likely to meet recommended levels of health-enhancing physical activity if they engaged in at least 60 minutes per week of structured exercise and sport therapy or in at least 30 minutes of individually performed exercise and sport activity. Conclusions: Given that prolonged immobilization and sedentary behaviour have harmful effects on patients’ physical and mental well-being, promoting exercise and sport activities is an important endeavour in psychiatric care. Clinics currently succeed in involving between 50-60% of all patients in sufficient physical activity. While this is encouraging, more systematic efforts are needed to ensure that all patients get enough physical activity.